Dugo sa buhangin - Poe, Fernando Jr.; Gamboa, Helen; Diaz, Paquito; Reyes, Efren; Gozon, Ruben T. (Manila Aquarius Records & Tapes, 1967)
Daniel, (FPJ) adopted son of El Tigre, (Johnny Montero) wanted by the law, with a price on his head. Wounded in an encounter, he managed to escape and hid in a farmer's hut. His hiding place was discovered by the farmer's daughter Carmen (Helen Gamboa), engaged to be married, yet was attracted to Daniel. She fed and cared for him. Regaining his strength he went back to El Tigre. Kidnap for ransom was the style of the bandit group, and Helen Gamboa fell victim to the group. In his desire to kill El Tigre, Daniel returned Helen back when she tried to escape to win the trust of the leader, only to assist her and make good their escape together. They managed to defeat the group, and finally decided to stay together bound by love.
DVD
Executive producers, Atty. Ruben T. Gozon ; director, Efren Reyes.
Fernando Poe Jr., Helen Gamboa, Paquito Diaz, Johnny Montero, Victor Bravo, Lito Anzures.
Keywords: Dugo ng buhangin (Motion picture).; Action and adventure films; Feature films